Ο Ρόλος Των Επαγγελματιών Υγείας Στη Διαχείριση της Ενδοοικογενειακής Βίας Κατά Των Γυναικών - Παναγιώτου, Αρετή (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Introduction: the Phenomenon of Domestic violence is one of the most serious and complicated social matters that all human sciences are called to deal with. Violence used to be a secret family matter but gradually it’s becoming a social problem. Aim: to highlight the contribution of the role of health care providers in the management od domestic violence against women. Material-Method: the method used was the search of the Greek and international literature in databases Google Scholar and Medline by keywords: domestic violence, women, abuse, health care providers. Results: Through the search of the literature found that a small percentage of women ask their doctor about domestic violence, although a large proportion of women classified for routine research on family violence. The highest testing rates were derived from the ratings of gynaecologists-obstetricians female while the lowest were associated control by emergency physicians. Also, the nurses suggested that interventions should focus on providing nursing care, while the main barrier identified for fear of reprisals on the part of the perpetrator. Conclusion: it is noticed that the assistance and support of women victims of domestic violence is a moral obligation for the health care providers. The intervention strategies for the confrontation of domestic violence should aim to directly help victims and prevent violent episodes.
Keywords: Domestic Violence; Family violence